2013
DOI: 10.1186/1744-9081-9-43
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the mGluR5 antagonist MPEP on ethanol withdrawal induced anxiety-like syndrome in rats

Abstract: Abstinence from chronic ethanol consumption leads to the manifestation of a variety of symptoms attributed to central nervous system hyperexcitability, such as increased irritability, anxiety, and restlessness. Recent studies have demonstrated the importance of metabotropic glutamate receptor 5 (mGluR5) in addictive behaviours. This study investigates the effects of the mGluR5 antagonist 2-methyl-6-(phenylethynyl)-pyridine (MPEP) on ethanol withdrawal induced anxiety using two behavioural paradigms. Male Wista… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
19
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 47 publications
5
19
0
Order By: Relevance
“…In particular, the up-regulation of different subunits of the NMDA receptor may cause hyperexcitability of the CNS during withdrawal or negative emotions such as dysphoria, irritability, anxiety, and depression (BlancoGandía et al, 2015). In accordance with numerous data in the literature, ethanol withdrawal induces an anxiogenic effect in the elevated plus-maze (Kumar et al, 2013;Van Skike, Diaz-Granados, Matthews, 2015). However, these findings contrast our previous data indicating that lower doses of ethanol produce anxiolytic-like effects (Cruz et al, 2012a).…”
Section: Silencesupporting
confidence: 91%
“…In particular, the up-regulation of different subunits of the NMDA receptor may cause hyperexcitability of the CNS during withdrawal or negative emotions such as dysphoria, irritability, anxiety, and depression (BlancoGandía et al, 2015). In accordance with numerous data in the literature, ethanol withdrawal induces an anxiogenic effect in the elevated plus-maze (Kumar et al, 2013;Van Skike, Diaz-Granados, Matthews, 2015). However, these findings contrast our previous data indicating that lower doses of ethanol produce anxiolytic-like effects (Cruz et al, 2012a).…”
Section: Silencesupporting
confidence: 91%
“…However, the analysis of closed arm entries did not indicate any differences between escalated, non-escalated, and naive rats. Additionally, evidence of a general reduction of motor function during alcohol withdrawal has been reported in rats (Kumar et al 2013; Williams et al 2012). The negative emotional state during acute withdrawal was also reflected by the development of mechanical hyperalgesia.…”
Section: Discussionmentioning
confidence: 95%
“…This study also found that pretreatment with mGlu5 antagonist MPEP dose-dependently reduced binge ethanol consumption in rodents. Others have shown that MPEP administration (10 mg/kg) attenuated ethanol withdrawal anxiety-like behaviors (Kumar et al, 2013) or have shown a reduction in ethanol reinstatement following acute MPEP administration elicited by drug-associated cues (Bäckström et al, 2004), as well as attenuation of ethanol withdrawal-elicited behaviors in rodents (Blendov and Harris, 2008). …”
Section: Discussionmentioning
confidence: 99%